Sustainable and active program – Development and application of SAVING methodology - Almeida-Silva, M.; Monteiro, A.; Carvalho, A.; Teixeira, A. M.; Moreira, J.; Tavares, D.; Tomás, T.; Coelho, A.; Manteigas, V. (International Journal of Environmental Research and Public Health, 2022)
The SAVING project aimed to create a sustainable and active aging program to promote the transition to sustainable aging in residential structures for the elderly (RSEs), developing research activities to apply the best strategies and good practices regarding the promotion of an active, healthy, and sustainable aging regarding social, economic, environmental, and pedagogic aspects. All this innovative methodology was built on a living-lab approach applied in one RSE, that was used as a case study. The results showed that the creation of the SAVING Brigade allowed not only increased reflection and mutual learning, but also created better conditions to face uncertainties and obstacles. Moreover, the use of indicators supported the basic themes and enabled comparison with other studies, between institutions or programs. Finally, the Action Plan acted as a tool for the development of previously defined strategies. It is possible to conclude that the breadth of the concept of quality of life encompasses the physical health of the individual, their psychological state, their social relationships, their perceptions, and the relationship with the characteristics of the context in which they are inserted. Therefore, active, sustainable, and healthy aging should be the goal. Keywords: aging; active; health; sustainability